Exploring the Effects of Changes in Design on the Analytical Uses of the NCVS Data - Cantor, David (Journal of quantitative criminology, 2005)
In 1992 changes were made in the design of the National Crime Victimization Survey (NCVS) to improve its accuracy and utility. Little is known about the effect of the redesign on the analytic uses of the NCVS. This paper examines the effects of the redesign across population subgroups important in analyses of victimization. This extends work on modeling victimization and begins the construction of a measurement model that addresses the reliability and validity of NCVS data across important analytic subgroups. These two goals are interrelated. If the redesign has a differential effect across subgroups, then it is critical to understand whether these effects increase or decrease the validity of the data. Assessing validity requires developing a model of survey response against which the results of the redesign can be compared. If differences across designs are consistent with expectation from the survey response model, then we can use these new data for substantive analyses. The design change had little effect on models of victimization. The effects observed were largely consistent with expectation from a survey response model except in the simple assault model, where the effects of age and income on victimization were reduced in the new design.